Digital transformation in engineering management : case studies of digital transformation in Africa - Telukdarie, Arnesh (Emmerald Publishing Limited, 2025)
Digital Transformation in Engineering Management presents real-world case studies that provide a unique perspective on current trends and challenges presented by digital transformation. It is an essential guide for practitioners and researchers seeking to understand the transformative potential of digitalisation. This book is a zribute to the outstanding individuals who are at the forefront of driving change through innovation and to the professionals who are tirelessly working towaards harnessing the immense power of digitalisation. Their hard work and dedication are instrumental in shaping a future where technology plays a pivotal role in enhancing our lives in ways we have yet to imagine. We are immensely grateful to these exceptional indivituals for their relentless efforts to push the boundaries of what's possible and for their unwavering commitment to creating a better, more advanced future. We hope that their work will continue to inspire and contribute to the advancement of technology in the years to come